1986
DOI: 10.1073/pnas.83.22.8654
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the boundaries between adjacent rapidly and slowly evolving genomic regions in Drosophila.

Abstract: The site of a dramatic change in the rate of DNA sequence evolution exists near the 68C glue gene clusters of several Drosophila species. We have previously determined the approximate location of this transition site by comparison of restriction maps of the regions flanking the 68C-like glue gene cluster of five members of the melanogaster species subgroup. In the present work we report the sequence of the transition region in three of these Drosophila species: D. melanogaster, D. yakuba, and D. erecta. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…One early study (Martin and Meyerowitz 1986) reported a 2-kb region of noncoding DNA near the glue gene cluster of three Drosophila species, which contained an abrupt boundary between a conserved region and a nonconserved region with a 10-fold elevated substitution rate, but this report has not been followed up with more extensive analyses based on complete genome sequence data. An abrupt boundary of evolutionary rates also occurs on the mammalian X chromosome at the junction between the pseudoautosomal region and the X-specific region.…”
Section: Discussionmentioning
confidence: 99%
“…One early study (Martin and Meyerowitz 1986) reported a 2-kb region of noncoding DNA near the glue gene cluster of three Drosophila species, which contained an abrupt boundary between a conserved region and a nonconserved region with a 10-fold elevated substitution rate, but this report has not been followed up with more extensive analyses based on complete genome sequence data. An abrupt boundary of evolutionary rates also occurs on the mammalian X chromosome at the junction between the pseudoautosomal region and the X-specific region.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of glue proteins, however, it is hard to believe that the survival of the flies is dependent on a specific composition of glue, because completely different patterns have been reported in wildtype strains of D. melanogaster (Beckendorf & Kafatos, 1976;Korge, 1977;Velissariou & Ashburner, 1980), in D. hydei (Ramesh & Kalisch, unpublished), and in others (Manousis, 1985). In this connection, one also has to consider the possibility that the genome posesses the ability to regulate differentially the rate of evolution of DNA sequences in different chromosomal locations (Martin & Meyerowitz, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore we think that these subregions are functionally important in evolution--for example, for Amy genes or for other genes. Alternatively, these region may just have lower mutation rates, as suggested in other regions of Drosophila genome (Martin and Myerowitz 1986;Werman et al 1990). Further analyses mutagenizing these subregions or finding strains having structural changes in these regions may resolve this issue.…”
Section: Importance Of This Region In Evolutionmentioning
confidence: 99%